تأثير ممارسة النشاط الرياضي للمناهج الدراسية على بعض بروتينات المناعة لطالبات جامعة بني سويف - جهاد جمال عويس; اشرف عبدالسلام العباسي; محمد حسين أحمد (Beni-Suef University, Faculty of Physical Education, 2022)
المستخلص باللغة العربية. يهدف هذا البحث الى التعرف على تأثير النشاط الرياضي الدراسي على بعض بروتينات المناعة لطالبات جامعة بني سويف لدى العينة قيد البحث والتعرف على الفروق في قياسات ترکيز بروتينات المناعة(IgG - IgM - TLC)،واستخدم الباحثون المنهج التجريبي، واشتملت عينة البحث على(50) طالبه مقسمة إلى(15 طالبة من کلية التربية الرياضية وتمثل المجموعة التجريبه) و(15) طالبة من کلية الطفولة المبکره وتمثل المجموعة الضابطة) و(20) طالبة تمثل الدراسه الاستطلاعية، وکانت من أهم النتائج أن النشاط الرياضى والانتظام فى ممارسته له تأثير فعال على بعض بروتينات المناعة وتوصى الباحثة حث الطالبات على ضرورة ممارسة النشاط الرياضي بانتظام ورفع مستوى الثقافة الصحية لدى الطالبات بصفه خاصة والمجتمع بصفه عامة. Abstract in English This research aims to identify the effect of academic sports activity on some immune proteins of Beni Suef University students in the sample under research and to identify the differences in the measurements of the concentration of immune proteins (IgG - IgM - TLC), and the researchers used the experimental method, and the research sample included (50) A female student divided into (15) female students from the College of Physical Education representing the experimental group, (15) female students from the College of Early Childhood representing the control group) and (20) female students representing the exploratory study. Some proteins of immunity The researcher recommends urging students to exercise regularly and raise the level of health culture among students in particular and society in general.